Accurate recording of personality disorder in clinical practice - Tyrer, Peter (BJPsych Bull, 2018)
Disturbances of personality are recorded very poorly in official statistics, but there are signs that this is changing. For many years, personality disorder has been either regarded as a secondary diagnosis that can be forgotten in the presence of another mental disorder, or avoided as the diagnosis gives the impression of untreatability or stigma. What is now abundantly clear is that under-diagnosis of personality disorder represents a disservice to patients and practitioners. It prevents a proper understanding of the longitudinal course of psychiatric disorder and an appreciation of some of the positive aspects of abnormal personality that can be used in treatment. We must no longer bury personality disorder, ostrich-like, in the diagnostic sand. It is there for the asking and needs to be embraced honestly and without fear if we are to improve the management of psychiatric patients. DECLARATION OF INTEREST: None.